A methodological framework to evaluate the impact of disruptions on airport turnaround operations: A case study. Issue 2 (June 2020) - Postorino, Maria Nadia; Mantecchini, Luca; Malandri, Caterina; Paganelli, Filippo
Highlights: A framework is proposed to determine impacts of airport airside disruptions. Airport airside operations are modelled by using an element-by-element approach. A discrete- event simulation model is built of both LTO and turnaround operations. The model allows to capture knock-on effects on successive operations. The methodology is illustrated through the case study of a large Italian airport. Abstract: The efficiency and quality of airport airside operations are frequently compromised by various, unexpected disruptive events such as bad weather conditions, lack of handling staff and/or resources, strikes, aircraft diversions or technical failures, which may reduce airport airside operating capacity and affect the punctuality and regularity of the operations. In particular, disruptive events could lead to a substantial deviation of aircraft operations from the schedule, by causing the reduction of the system capacity and, thus, increasing congestion and flight delays, which worsen the overall performance of the air transport system. In this paper, the effects of unexpected events, particularly magnitude and duration, affecting airport airside operations are estimated within a general framework based on an element-by-element approach, adopted for the detailed representation and simulation of aircraft airside operations. The impacts generated by airport airside unexpected disruptions are modelled by using a discrete-event simulation model, dealing with both aircraft landing-and-takeoff (LTO) cycles and turnaround operations, developed and applied to the test case of a large regional airport.